2018
DOI: 10.1111/ijpp.12458
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from the public’s understanding of drug information and safety? A population survey

Abstract: The public has great interest in useful information about all aspects involved in the use of medicines. This includes consumer reporting of suspected ADR, which is still unknown to many people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The majority (43.1%) of participants reported that they always read the PIL which aligns with the findings of several studies from other countries [20,26,27]. A study in Spain mentioned that 61.4% of participants always read the PIL [20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The majority (43.1%) of participants reported that they always read the PIL which aligns with the findings of several studies from other countries [20,26,27]. A study in Spain mentioned that 61.4% of participants always read the PIL [20].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, a dedicated drug information service is available in healthcare settings of the Dammam region [23]. The score indicated adequate knowledge about medication use which was in line with the results reported by Salgueiro et al [20]. The score suggests good knowledge about medications among patients who were above 45, employed and married.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Currently the black triangle and the accompanying statement are only present in the SmPC and PL. Previous research suggest that many patients find PLs hard to comprehend and have difficulties in finding the information they are looking for [21][22][23]. Many patients do not either read the PL [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggest that many patients find PLs hard to comprehend and have difficulties in finding the information they are looking for [21][22][23]. Many patients do not either read the PL [21][22][23]. Adding the additional monitoring information also to outer packaging might help in raising awareness especially among the public.…”
Section: Discussionmentioning
confidence: 99%